Experimental study of ELM-like heat loading on beryllium under ITER operational conditions. (12th January 2016) - Spilker, B; Linke, J; Pintsuk, G; Wirtz, M
Abstract: The experimental fusion reactor ITER, currently under construction in Cadarache, France, is transferring the nuclear fusion research to the power plant scale. ITER's first wall (FW), armoured by beryllium, is subjected to high steady state and transient power loads. Transient events like edge localized modes not only deposit power densities of up to 1.0 GW m −2 for 0.2–0.5 ms in the divertor of the machine, but also affect the FW to a considerable extent. Therefore, a detailed study was performed, in which transient power loads with absorbed power densities of up to 1.0 GW m −2 were applied by the electron beam facility JUDITH 1 on beryllium specimens at base temperatures of up to 300 °C. The induced damage was evaluated by means of scanning electron microscopy and laser profilometry. As a result, the observed damage was highly dependent on the base temperatures and absorbed power densities. In addition, five different classes of damage, ranging from 'no damage' to 'crack network plus melting', were defined and used to locate the damage, cracking, and melting thresholds within the tested parameter space.